Empathie et cruauté : le paradoxe de l’imaginaire des viandes au XVIIIe siècle - Capucine Lebreton (Astérion, 2018)
XVIIIth-century writings about the habit of eating meat deal with problems that are only addressed today when defending animal rights, such as the sensibility of animals that are killed for their flesh or what human beings become through the process of eating meat. But in the XVIIIth century this kind of discourse doesn’t belong to animal rights activists, and is even paradoxically exempt from practical consequences: writers who deplore the eating of animal flesh however don’t ask their fellow humans to cease this consumption. How do western XVIIIth-century thinkers solve this paradox: emphasizing empathy with animals, while at the same time killing them to eat their flesh? Through philosophic and medical XVIIIth-century writings dealing with the consequences of eating meat, this paper examines the representation of mankind underlying a discourse that belongs nowadays to meat diet’s subconscious.